Shared Reading to Enhance Students Reading Skills - Samba, Agustinus Malo (STKIP Harapan Bima, 2022)
The purpose of this study was to determine that the Shared Reading learning model can Enhance the cognitive learning outcomes of grade VII students in reading comprehension at SMPN 3 Wewewa Timur. Each cycle consists of stages of planning, action, observation, and reflection. The instruments used are student tests, student activities, and teachers using observation sheets, at the end of each cycle. The results showed that the application of the Shared Reading learning model can Enhance students' cognitive competence. The percentage of students' classical achievement in cognitive competence increases over time. In the pre-cycle, the percentage is 46% (not enough), in cycle I it is 50% (not enough) and in cycle II it is 92% (very good). Meanwhile, the percentage of student activity also increased. In the pre-cycle, the percentage is 52% (sufficient), in cycle I it is 64% (good) and in cycle II it is 80% (very good). From the findings, it proves that the application of the Shared Reading learning model can Enhance cognitive competence and student activity in grade VII SMPN 3 Wewewa Timur.